Multimodal Imaging in Retinal Vascular Occlusions following Trauma – A Case of Sickle Cell Disease with Negative Sickling Test - Ekta Singh Sahu; Mani Sachdeva; Alok Sen; Samendra Karkhur (Journal of Ophthalmic & Vision Research)
Abstract